Learning to read and write in bilingual contexts. A study and implementation programme with indigenous qom communities in Argentina - Rosemberg, Celia Renata (2012)
This paper presents a bilingual and intercultural programme carried out with young children from indigenous Qom communities located in different areas throughout Argentina. The programme seeks to promote learning and avoid the problems that these children often meet throughout the literacy acquisition process. Within a theoretical framework that combines psycholinguistic theories that recover the central tenets of the sociocultural perspective (Nelson, 1996, 2007), and literacy approaches from an intercultural perspective (Rosemberg, Borzone & Diuk, 2003) we developed a series of educational materials to promote the learning of literacy in Qom and in Spanish to Qom children. The study articulates collaboration between researchers, teachers and community members, who selected community situations to be observed and carried out observation records. These records were used to write “ethnographic reading books”, intercultural storybooks that are used in the literacy settings. These “ethnographic books” reflect the children's knowledge of their own dialect and community while integrating these with the standard language variety and other types of knowledge.